Impacts of gender bias - A L Khalib; A A Suriyati (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2007)
Gender bias are most obvious in the distribution of income and wealth. This reflects women’s unequal position in the labour market , their less favorable treatment in most social security systems and their lower status within the household. Discrimination against women is also evident in the political sphere. Their access to power is not commensurate with their numbers, their needs or their contributions as citizens. As well as affecting women’s physical and mental health, gender bias also affect the quality of the services they receive. In most developed countries, women are offered equal access to basic health care. However their use of those service may be hindered by a number of gender related factors which are likely to affect poor women in particular. In health organization, gender bias gives significant impact to the evaluation of staff performance, increase stress level and miscommunication. It is also influence the leadership style and also can create ‘glass ceiling’ phenomenon. Job dissatisfaction , absenteeism and high turn over are also the consequences of gender bias. Alongside the development of gender sensitive methods of routine data collection, gender bias in health research will also need to be addressed. Most biomedical research continues to be based on the unstated assumption that women and men are physiologically similar in all respects apart from their reproductive systems. Other biological differences are ignored, as are the social/gender differences that have such a major impact on health.